Long-Run Exchange Rate Dynamics : A Panel Data Study - Habermeier, Karl (IMF Working Papers; Working Paper ;, 1999)
Long-run movements of real exchange rates are studied using a panel data set comprising 51 economies. The purchasing power parity hypothesis (PPP) is examined first using unit root tests. It is found that PPP does not hold for the full sample of countries, but it may hold for the advanced economies, as well as open and high-inflation economies. Using the recently developed mean group and pooled mean group estimators, the paper finds support for the Balassa-Samuelson hypothesis in both advanced and developing economies; and for the influence of shifts in the terms of trade.